Amin Al-Khuli dan Metode Tafsir Sastrawi Atas Al-Qur'an - Ramadhani, Wali (At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2017)
This article discusses about the biography of Amin al-Khuli and his thought; literary interpretation of the Quran (TafsirSastrawi). He offers this method because the Quran is Arabic(?arabiyyunmubin). Therefore, the understanding of the Quran can only be revealed by using literary interpretation (tafsirsastrawi). This method has two important studies: the study of the external Quran (dirasah mahawla al-Qur?an) and the study of the internal Quran (dirasah ma fi al-Qur?an)